ANALISIS KEPUASAN KONSUMEN TERHADAP LAYANAN PASAR MODERN DI KOTA BENGKULU - Wahyudin, Wahyudin; Suryanty, Melli; Badrudin, Redy (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
This research was conducted in modern markets in Bengkulu City in March 2018 with 96 samples. This study aims to identify the attributes that need to be developed and maintained in achieving customer satisfaction and to know the level of customer satisfaction with modern market services in Bengkulu City. The purpose of the first analyzed by Importance Performance Analysis (IPA) method and the purpose of the second analyzed by Customer Satisfaction Index (CSI) method. Based on the results obtained from the calculation of IPA, attributes that need to be improved on the modern market is the state of the market building, the completeness of market products, and the guarantee of the quality and quantity of goods. As for the attributes that need to be maintained the achievement includes the layout of the market, the convenience of the market, the accuracy in serving, the speed in serving, the responsiveness in serving, polite and courteous in serving, guarantee the price of goods, market security guarantee, honest in serving, and appreciate the consumers. While for the results of the calculation of consumer satisfaction index found the value of CSI in modern markets by 70%.